LIMAQUA : African interdisciplinary laboratory in sustainable, nutritition-sensitive marine aquaculture [résumé] - (:unkn) unknown (My University, 2022)
AASA : Aquaculture Association of Southern Africa, Stellenbosch, ZAF, 11-/07/2022 - 14/07/2022
Keywords: African Research